Student-Generated Podcast: An Innovative Learning Tool to Develop English Speaking Skill in Higher Education - Nuzul Hijrah Safitri; Aminah Maulida Nugraha Silawati (CV. Mitkom Indotama, 2025)
Speaking skill is the most essential aspect of English because it enables learners to communicate effectively in real-life situations. However, especially in Indonesian higher education context, many students struggle with fluency, pronunciation, and confidence when speaking in English. Therefore, this study discusses the use of student-generated podcast as a learning tool to promote English speaking skill in higher education. This study is a literature review that obtains data related to the topic from research articles and relevant books. This study reveals that student-generated podcast can be an effective learning tool to enhance students’ speaking skill in which students generate their own podcast through scripting, recording, editing and publishing. Besides, this activity is also beneficial for students in increasing motivation and confidence, fostering collaborative learning, and developing transferable skills. Nevertheless, there are some challenges faced by students during podcast production including a lack of familiarity of podcasting tools and editing software, and a lack of technical skills. Therefore, students should be directed during the production process and given access to the right resources so that student-generated podcast can be an effective learning tool to improve students’ speaking skill in EFL classroom.